Quotient Frames and Filters - .THUMBAKARA, RAJESH. K (IJRDO -JOURNAL OF MATHEMATICS, 2016)
Frame theory is the study of topology based on its open set lattice and it was studied extensively by various authors. In this paper we introduce the notion of quotient frames using filters and study the relation between the filters of the given frame and the filters of the corresponding quotient frame.